Statin treatment: myths and reality - L. A. Malay; B. V. Sharykin; A. N. Miroshnichenko; V. V. Konurovsky; E. E. Kusnetsova; O. I. Vasina (Кардиоваскулярная терапия и профилактика)
Aim. To assess effectiveness and tolerability of rosuvastatin treatment, as a part of primary and secondary cardiovascular prevention, in patients with high and very high cardiovascular risk and dyslipidemia.Material and methods. Forty patients received rosuvastatin (starting dose 10 mg/d) for 12 weeks. At baseline, medical history collection, physical and instrumental examination, blood biochemical assay (creatinine, glucose, lipids, aminotransferase, bilirubin, urea levels) and general urine assay were performed. Four and 12 weeks later, complex assessment of rosuvastatin effectiveness and safety took place. If target levels of low- or high-density lipoprotein cholesterol (FDF-CH, <2,6 mmol/1; HDF-CH, >1,2 mmol/1) were not achieved, rosuvastatin dose increased up to 20 mg/d. After 4 and 12 weeks, all parameters measured previously were re-assessed, including patients' complaints, therapy compliance, and adverse effects, if any.Results. After 4 and 12 weeks of rosuvastatin treatment, lipid profile normalized in most patients, target FDF-CH, HDF-CH, and triglyceride levels were achieved in 63 %, 65 %, and 68 %, respectively. Mean rosuvastatin dose was 10,6 mg/d. Fhe medication was well tolerated.Conclusion. Rosuvastatin demonstrated not only high lipid-lowering effectiveness, but also good tolerability.